2021
DOI: 10.4103/cjp.cjp_38_21
|View full text |Cite
|
Sign up to set email alerts
|

Participation of Nitrogen Oxide and Its Metabolites in the Genesis of Hyperimmune Inflammation in COVID-19

Abstract: Despite the success in the tactics of treating COVID-19, there are many unexplored issues related to the development and progression of the process in the lungs, brain, and other organs, as well as the role of individual elements, in particular, nitric oxide (NO), and in the pathogenesis of organ damage. Based on the analyzed literature data, we considered a possible pathophysiological mechanism of action of NO and its derivatives in COVID-19. It can be noted that hyperimmune systemic inflammation and “cytokin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 127 publications
0
3
0
Order By: Relevance
“… Paraoxonase COVID-19 PON1 (serum paraoxonase 1) has been demonstrated to increase protein levels from non-severe to severe patients [74] . Peroxynitrite The overproduction of peroxynitrite exacerbates the severity of the COVID-19 [102] . ROS In vitro studies have found that Covid-19 infection increases ROS production in human promonocyte cells and various mammalian cells [103] .…”
Section: Markers Of Oxidative Stress In Covid-19mentioning
confidence: 99%
“… Paraoxonase COVID-19 PON1 (serum paraoxonase 1) has been demonstrated to increase protein levels from non-severe to severe patients [74] . Peroxynitrite The overproduction of peroxynitrite exacerbates the severity of the COVID-19 [102] . ROS In vitro studies have found that Covid-19 infection increases ROS production in human promonocyte cells and various mammalian cells [103] .…”
Section: Markers Of Oxidative Stress In Covid-19mentioning
confidence: 99%
“…COVID-19, an infection caused by the severe-acute-respiratory-syndrome-related coronavirus 2 (SARS-CoV-2), can be asymptomatic or can produce mild or severe symptoms that can lead to life-threatening multiorgan failure in patients 1 , 2 . The severity of symptoms is evaluated with the use of diagnostic scales, including the Modified Early Warning Score (MEWS) 3 , 4 An infection with the SARS-CoV-2 virus triggers excessive production of reactive oxygen species (ROS) 5 and reactive nitrogen species (RNS) 6 , which enhances protein glycoxidation 7 , 8 . In patients who had experienced severe symptoms, as well as mild and moderate symptoms of COVID-19, these processes are intensified and can lead to various complications 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, the European Food Safety Authority has approved HXT as a means of protecting the cardiovascular system. From a theoretical point of view, we study the interaction between HXT and arginine to stop the production of harmful peroxynitrite, which is responsible for pneumonia and numerous organ failures associated with COVID-19 [13].…”
Section: Introductionmentioning
confidence: 99%